The Clean-Label-Friendly Solution: Stabilizing Milk-Based Cocoa Beverages with Citrus Fiber - Ozturk, Saniye Akyil; Kamer, Deniz Damla Altan; Karaca, Ali Can; Toker, Omer Said (AMER CHEMICAL SOC, 2025)
The increasing demand for clean label products has driven the development of natural and sustainable stabilizers in the food industry. This study investigates the potential of citrus fiber as a clean-label-friendly ingredient to improve the stability of cocoa-based dairy beverages. A Central Composite Rotatable Design (CCRD) was employed to evaluate the effects of homogenization pressure (100-300 bar) and citrus fiber concentration (0.10-0.40%) on the water-holding capacity (WHC), sedimentation, creaming index, pH, viscosity, and torque. Analytical methods including zeta potential, FTIR, particle size distribution, microscopy, and SEM-EDS were utilized to assess the structural properties and stability of the formulations. The results demonstrated significant improvements under optimal conditions that citrus fiber significantly enhanced WHC (95.95%), minimized sedimentation (0%) with creaming index (0%), and improved viscosity (197.22 mPas), contributing to a homogeneous dispersion of cocoa particles. Homogenization pressure and citrus fiber concentration exhibited synergistic effects, optimizing the physical stability of the beverage. Zeta potential (-27.90 mV) and particle size (630.53 nm) distribution analysis indicated improved electrostatic stability and reduced particle aggregation, while FTIR revealed interactions between citrus fibers and cocoa components. Microscopic analysis, molecular docking, and SEM-EDS further confirmed the structural integration of citrus fiber and proteins, reducing sedimentation and creaming index phenomena. This study underscores the functional advantages of citrus fibers as a natural stabilizer, offering a clean, label-friendly solution for the dairy beverage industry. The findings provide valuable insights for product formulation and process optimization, paving the way for the development of stable, high-quality cocoa-based dairy beverages that align with sustainable ingredients.
Keywords: PROTEIN; FOOD; TEMPERATURE; PARTICLES; EMULSIONS; PRESSURE; RHEOLOGY; SHEAR; Chemistry